Internationalization of tertiary education services in Singapore - Mun-Heng Toh (Asian Development Bank Institute (ADBI), 2012)
This paper traces the development of the education sector from its nascent stage of serving economic development needs to the internationalization stage of fulfilling Singapore's aspiration to be a global education hub. The state plays an important role in guiding and fostering development of the education sector in the creation and production of human capital for domestic production as well as cross-border trading to generate income and employment, and attract talent to the economy. Regional trading agreements can play a facilitating role for internationalization of higher education services, especially when commitments under the General Agreement on Trade in Services (GATS) are weak. Private education enterprises need no less regulatory measures than other economic sectors to function properly in the market economy - to add value, assure quality services, and yield benefits for education services purchasers.
Keywords: F16; I23; J24; 330; education sector; Singapore; internationalization of education; tertiary education services; economic development; higher education services; Hochschule; Dienstleistung; Handelsabkommen; GATS; Standortfaktor; Singapur